Randomized Study of Darbepoetin Alfa and Recombinant Human Erythropoietin for Treatment of Renal Anemia in Chronic Renal Failure Patients Receiving Peritoneal Dialysis - Wen-Yi Li; Tzong-Shinn Chu; Jenq-Wen Huang; Ming-Shiou Wu; Kwan-Dun Wu (Journal of the Formosan Medical Association, 2008)
Darbepoetin alfa can be administered less frequently than recombinant human erythropoietin (r-HuEPO) for the treatment of anemia in chronic renal failure (CRF) patients. We aimed to confirm that darbepoetin alfa at a reduced dosing schedule can safely maintain a target hemoglobin level in CRF patients undergoing peritoneal dialysis. Methods: Forty-five PD patients receiving r-HuEPO were randomized in a 1:1 ratio to continue r-HuEPO or to change to darbepoetin alfa (open-label). Patients were maintained within a target range of hemoglobin for 5.5 months by adjusting the dose and then the frequency of darbepoetin alfa and r-HuEPO over the initial 4 months. The evaluation period was the final 1.5 months. A total of 37 patients completed the study. Results: During the evaluation period, the hemoglobin of the darbepoetin alfa group was higher than that in the baseline period (10.46 ± 0.22 g/dL vs. 9.98 ± 0.18 g/dL, p < 0.05). Hemoglobin remained similar in the r-HuEPO group. The average dose in the darbepoetin alfa group was 93.0 μg/month, while the average dose in the r-HuEPO group was 18,339.9 units/month. The dosing frequency was less in the darbepoetin alfa group (3.9 times/month vs. 9.2 times/month). We divided the darbepoetin alfa group into low-dose (< 70 μg/month) and high-dose (≥ 70 μg/month) subgroups. The body weight in the high-dose group was higher than that in the low-dose group (66 ± 11 kg vs. 52 ± 4.4 kg, p < 0.01). Conclusion: Both darbepoetin alfa and r-HuEPO safely maintain hemoglobin levels within the target range in peritoneal dialysis patients.